Влияние динамического режима подвода тепла на характеристики зажигания ВЭМ; Известия вузов. Физика; Т. 57, № 8/2 - Архипов В. А. Владимир Афанасьевич; Коротких А. Г. Александр Геннадьевич; Кузнецов В. Т. Валерий Тихонович; Жуков А. С. Александр Степанович (2014, 2014)
Заглавие с экрана